Implementation of Educational Supervision in the Etnik Kreatif Nusantara Special School - Anisa Rahma Nada; Asmendri (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2022)
This research in interactive qualitative research with a descriptive approach that aims to explore in-depth information about the Implementation of educational supervision at SLB Etnik Kreatif Nusantara. Data were obtained through observation on three main objects, namely the curriculum, Human Resources and facilities and infrastructure. Based on failed data, shows that there are obstacles in the Implementation of curriculum Supervision. Meanwhile, Supervision in the field of Human Resources can run well. This study aims to introduce the Typical Example of educational supervision and the performance of school principals in accommodating also improving the quality of education in developing learning that covered schools. This paper uses a qualitative approach with a literature study method that takes several references from various literatures.